The Impact of Religiosity on Psychological Well-Being Among Women Victims of Elephant Attacks - karjuniwati, karjuniwati; Zuanny, Iyulen Pebri; Nasruddin, Nasruddin; Safrilsyah, Safrilsyah; Muslim, Muslim; Alka, Muhammad; Wijayaningsih, Renita; Fuadi, Zahrul; Larasita, Puja (Psikoislamedia: Jurnal Psikologi, 2025)
Women who are victims of elephant attacks often experience fear in carrying out daily activities, impacting their psychological well-being. This study examines religiosity as a factor influencing their psychological resilience amid frequent elephant incursions into residential areas. The purpose of the research was to determine the effect of religiosity on the psychological well-being of these women. The study used religiosity and psychological well-being scales as measuring instruments, with purposive sampling and a total sample of 22 participants. Data were analyzed using simple linear regression, yielding a significant value of 0.013 (p < 0.05), indicating a significant effect. The R Square value was 0.271, meaning religiosity accounts for 27.1% of the variance in psychological well-being, while 72.9% is influenced by other factors. These findings highlight the important role of religiosity in helping women maintain psychological well-being despite the ongoing threat of elephant attacks.